2014
DOI: 10.53761/1.11.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Features of Engaging and Empowering Experiential Learning Programs for College Students

Abstract: This study describes three collegiate programs that have a high interest in creating engaging learning environments outside of the classroom. The three settings in this study are a three-year degree granting college focusing on internship-based learning, a nationally recognized service-learning program at a private university, and a small private college emphasizing work and service. Research was guided by two exploratory questions: (1) How can students, faculty, administrators, and community partners’ work to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…From a pedagogical perspective, The Collaborative enables Work-Integrated Learning (WIL) that may include approaches of problem-based learning, project-based learning, experiential learning and service-learning. It most closely aligns with the service-learning pedagogy, focusing not just on increasing student learning and development, but also on addressing social needs and promoting social change (Perrin, 2014). One could argue that this applies not only to students' learning, but also to academic staff.…”
Section: The Collaborative Modelmentioning
confidence: 96%
“…From a pedagogical perspective, The Collaborative enables Work-Integrated Learning (WIL) that may include approaches of problem-based learning, project-based learning, experiential learning and service-learning. It most closely aligns with the service-learning pedagogy, focusing not just on increasing student learning and development, but also on addressing social needs and promoting social change (Perrin, 2014). One could argue that this applies not only to students' learning, but also to academic staff.…”
Section: The Collaborative Modelmentioning
confidence: 96%
“…Previous research has consistently shown that active participation in social annotation activities correlates with improved learning outcomes and a greater benefit from insights contributed by peers (e.g., [21,28,49]). Furthermore, peer support plays a pivotal role in motivating individuals to engage in autonomous learning environments, where instructors typically take a less active role in guiding discussions [12,36].…”
Section: Peer Acknowledgement Facilitates Learners' Social Annotation...mentioning
confidence: 99%
“…WIL and reflective practice enable integration of theory and practice to develop nuanced knowledge and skills in a variety of professions, including teaching (Ramsaroop & Petersen, 2020) and medicine (Hargreaves, 2016). Real-life scenarios, project-based learning, case studies, role-plays and simulations incorporating cooperative learning pedagogies and teamwork assessment tasks can promote application of theory to practice while developing various soft skills and can potentially be delivered in person or online (Kelton & Kingsmill, 2016;Low et al, 2021;Mueller et al, 2022;Perrin, 2014;Tsiligiris & Bowyer, 2021).…”
Section: Pedagogies and Assessment For Employabilitymentioning
confidence: 99%